The Subculture of Violence and the Criminal Subculture - Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
Theoretical concepts of the subculture of violence and the criminal subculture have appeared within the framework of the criminological theory as a result of the need to view the complex phenomena of violence and crime in connection with the cultural context in which they appear. In the social and cultural practice, the dynamic interaction of these social phenomena is constantly going on; cultural criminology has great potential for providing answers to the issues of the arising violence, violent crimes and other congenial phenomena. The paper gives a short overview of the theoretical aspect of the appearance and development of these subcultural concepts, and some ambiguities are discussed concerning their definition, especially the connection with the consumer-materialistic culture of developed capitalism. The basis of the subculture of violence, as well as criminal subculture, is made of the continuum of marginality as the central point of acceptance of violent and criminal values as the recognisable anti-cultural values. At the end of the paper, a resume is given on the possibilities and the significance of implementation of these concepts in the analysis of the Serbian society, since it persistently moves within the domains of these two criminological-subcultural concepts.